Toward a Solution of the “Peruvian Puzzle”: Pelagic Food-Web Structure and Trophic Interactions in the Northern Humboldt Current Upwelling System Off Peru - Massing, Jana C.; Schukat, Anna; Auel, Holger; Auch, Dominik; Kittu, Leila; Pinedo Arteaga, Elda Luz; Correa Acosta, Jonathan; Hagen, Wilhelm (Frontiers in Marine Science, 2022)
The northern Humboldt Current upwelling system (HCS) belongs to the most productive marine ecosystems, providing five to eight times higher fisheries landings per unit area than other coastal upwelling systems. To solve this “Peruvian puzzle”, to elucidate the pelagic food-web structure and to better understand trophic interactions in the HCS, a combined stable isotope and fatty acid trophic biomarker approach was adopted for key zooplankton taxa and higher trophic positions with an extensive spatial coverage from 8.5 to 16°S and a vertical range down to 1,000 m depth. A pronounced regional shift by up to ∼5‰ in the δ15N baseline of the food web occurred from North to South. Besides regional shifts, δ15N ratios of particulate organic matter (POM) also tended to increase with depth, with differences of up to 3.8‰ between surface waters and the oxygen minimum zone. In consequence, suspension-feeding zooplankton permanently residing at depth had up to ∼6‰ higher δ15N signals than surface-living species or diel vertical migrants. The comprehensive data set covered over 20 zooplankton taxa and indicated that three crustacean species usually are key in the zooplankton community, i.e., the copepods Calanus chilensis at the surface and Eucalanus inermis in the pronounced OMZ and the krill Euphausia mucronata, resulting in an overall low number of major trophic pathways toward anchovies. In addition, the semi-pelagic squat lobster Pleuroncodes monodon appears to play a key role in the benthic-pelagic coupling, as indicated by highest δ13C’ ratios of −14.7‰. If feeding on benthic resources and by diel vertical migration, they provide a unique pathway for returning carbon and energy from the seafloor to the epipelagic layer, increasing the food supply for pelagic fish. Overall, these mechanisms result in a very efficient food chain, channeling energy toward higher trophic positions and partially explaining the “Peruvian puzzle” of enormous fish production in the HCS.